2019
DOI: 10.1126/sciadv.aau8535
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive chimera states in human brain networks

Abstract: The human brain is a complex dynamical system, and how cognition emerges from spatiotemporal patterns of regional brain activity remains an open question. As different regions dynamically interact to perform cognitive tasks, variable patterns of partial synchrony can be observed, forming chimera states. We propose that the spatial patterning of these states plays a fundamental role in the cognitive organization of the brain and present a cognitively informed, chimera-based framework to explore how large-scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 86 publications
(147 reference statements)
5
101
0
Order By: Relevance
“…This regime is denoted by letters INC in the regime diagram. The chimera-like structures are realized in the system (2), when values of the coupling strength and the coupling range increase. This regime is illustrated in a snapshot of the system state in Fig.2 and denoted by letters CL in the regimes diagram in Figs.…”
Section: Basic Dynamical Regimes Of the Lattice (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…This regime is denoted by letters INC in the regime diagram. The chimera-like structures are realized in the system (2), when values of the coupling strength and the coupling range increase. This regime is illustrated in a snapshot of the system state in Fig.2 and denoted by letters CL in the regimes diagram in Figs.…”
Section: Basic Dynamical Regimes Of the Lattice (2)mentioning
confidence: 99%
“…Moreover, the phase portrait projections for oscillators in the solitary state regime are very similar. It enables us to assume that the nature of the solitary state appearance is the same both inside the incoherence cluster and outside it in the lattice (2).…”
Section: Target Wave Chimeramentioning
confidence: 99%
“…In this study we discuss the dynamics of chimera states, defined by the coexistence of spatial regions with coherent and incoherent dynamics. They can be found in many reallife systems, like in superconducting quantum interference devices (SQUIDS) [15,16], the cognitive organization of the brain [17,18], in biological systems like self-propelled particles [19], or neural networks [20,21]. In addition, chimera states were found in quantum mechanics [22] or mechanical oscillators [23].…”
Section: Introductionmentioning
confidence: 99%
“…Chimera states were first discovered in 2002 in a system of coupled Kuramoto phase oscillators [1,2] and were further established 2 years later in a seminal work by Abrams and Strogatz [3]. They captivated scientific interest during the past 15 years due to their intriguing structural and dynamical properties and to potential applications in physics [4][5][6][7], chemistry [8][9][10], and biology [11][12][13][14][15][16]. Although original studies referred to coupled phase oscillators, later works have reported chimera states in coupled FitzHugh-Nagumo, Hindmarsh-Rose, Van der Pol, and Leaky Integrate-and-Fire (LIF) oscillator networks [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%